Wykorzystanie metody DEA do oceny ryzyka kredytowego przedsiębiorstw w ramach credit-scoringu - Feruś, Anna (The Application of DEA Method for Estimating of Companies' Credit Risk within the Framework of Credit-scoring, 2007)
The subject of the present article is to propose a new procedure forecasting credit risk in Polis! economy environment. The central aim of the article was to present the possibilities of implementing DEA method to estimate credit risk of companies on a concrete example. The research for the project was conducted on the basis of comparison of the suggested method with currently used procedures, that is point method discriminative analysis and linear regression. For the purpose of the project, the current data on 100 credit motions and enclosed notes on credit payment have been acquired from one of the banks. On the basis of the research carried out, it can be concluded that DEA method facilitate forecasting financial problems, including bankruptcy of companies in Polish economy conditions, an that its effectiveness is comparable to or even greater than approaches implemented so far.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 144-154